Illuminierte Urkunden. Beiträge aus Diplomatik, Kunstgeschichte und Digital Humanities / Illuminated Charters. Essays from Diplomatic, Art History and Digital Humanities Illuminated Charters. Essays from Diplomatic, Art History and Digital Humanities - Bartz, Gabriele; Gneiß, Markus (2019)
Illuminated documents have long been treated as research stepchildren. Not least because of the use of digital aids, they have increasingly come into the public eye in the past decade. The newly awakened research interest focuses on the changed performativity of certificates through the addition of decorative elements. The richly illustrated volume presents essays by researchers from eleven countries who examine illuminated certificates from different perspectives of their disciplines.